Application of data mining and machine learning on occupational health and safety struck-by incidents on south African construction sites: a CRISP-DM approach. - Adams, Logan Charl (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.